Privacy Enhanced Superdistribution of Layered Content with Trusted Access Control - CHONG, Daniel J. T. (Institutional Knowledge at Singapore Management University, 2006)
Traditional superdistribution approaches do not address consumer privacy issues and also do not reliably prevent the malicious consumer from indiscriminately copying and redistributing the decryption keys or the decrypted content. The layered nature of common digital content can also be exploited to efficiently provide the consumer with choices over the quality of the content, allowing him/her to pay less for lower quality consumption and vice versa. This paper presents a system that superdistributes encrypted layered content and (1) allows the consumer to select a quality level at which to decrypt and consume the content; (2) prevents the merchant from knowing which exact content package is consumed by the consumer, hence enhancing consumer privacy; and (3) through trusted access control, prevents the consumer from indiscriminately copying and redistributing the decryption keys or the decrypted content, thus achieving a form of digital rights management.